Remote Sensing Analysis Of Recent Carbonate Platforms East Of Sabah: Potential Analogues To Miocene Carbonate Platforms Of The South China Sea - CHALABI, AICHA (2012)
Modem carbonate platforms in the Celebes Sea, East of Sabah, were selected for a remote sensing analysis, aimed at mapping sedimentary facies and textures from high-resolution satellite imagery. The ultimate goal of this study is to develop present-day analogues to the Miocene platforms of the South China Sea and improve the accuracy of carbonate reservoir modeling in these ancient platforms. In order to generate facies maps of the modern carbonate platforms of the Celebes Sea, unsupervised classification method (I SODA TA algorithm) was applied to extract carbonate facies from Quickbird satellite image multispectral with 2.4m resolution. Initial facies maps were generated for Gaya, Selakan, Kapikan, Mantabuan, Church reef, Maiga and Sibuan platforms and were validated with the analysis of surface sediments. Hundred and forty (140) sediment samples were collected from these platforms and were analyzed for component identification, grain size distribution and sorting. The carbonate facies derived from high resolution satellite imagery include island, reef complex, carbonate sand shoal, grass-covered sand shoal, shallow lagoon and deep lagoon. Carbonate grain size analysis results show clear characters and properties typical of each mapped facies. In order to generate carbonate sediment texture maps, mean grain size and sorting maps were used to assign textural classes to each thematic class using ArcMap 9.3. Integration of field work data showed that wackestone to mudstone are found in the deep lagoon; packstone to wackestone is dominant in the shallow lagoons; Carbonate sand shoal class is characterized by grainstone to packstone and the reef complex is essentially made up of boundstone to rudstone. The results obtained from this study were used to estimate proportions of potential reservoir facies and determine the degree of heterogeneity in facies distribution on the various platforms. The depositional facies on small platforms (I to 5 km2) are ~onsistently good potential reservoirs and are homogeneously distributed, whereas large platforms (30-50km2) are characterized by a high degree of heterogeneity in surface facies distribution and a high proportion of poor potential reservoir facies.